2014
DOI: 10.1155/2014/691540
|View full text |Cite|
|
Sign up to set email alerts
|

Serum Fetuin-A Levels in Patients with Cardiovascular Disease: A Meta-Analysis

Abstract: Background. Fetuin-A (FA) suppresses arterial calcification, promotes insulin resistance, and appears to be elevated in patients with cardiovascular diseases (CVD), but the data is still inconsistent. To clarify the correlation between serum FA levels and the presence and severity of CVDs, we performed this meta-analysis. Method. Potential relevant studies were identified covering the following databases: PubMed, Embase, Web of Science, Cochrane Library, CISCOM, CINAHL, Google Scholar, China BioMedicine (CBM),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 36 publications
1
22
0
4
Order By: Relevance
“…Furthermore, decreased serum fetuin-A and albumin levels are associated with the development of coronary artery disease and heart valve calcification505152535455565758. Therefore, the risk factors of atherosclerosis and heart valve calcification are identical to those promoting the formation of CPB in the human blood.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, decreased serum fetuin-A and albumin levels are associated with the development of coronary artery disease and heart valve calcification505152535455565758. Therefore, the risk factors of atherosclerosis and heart valve calcification are identical to those promoting the formation of CPB in the human blood.…”
Section: Discussionmentioning
confidence: 99%
“…For example, decreased concentrations may directly limit cardiac functions by promoting cardiac fibrosis and calcification, resulting in CVD progression (Lim et al ., ). Low levels were a valid predictor of CVD in previous prospective studies (Kadoglou et al ., ; Sun et al ., ) and have been linked to CVDs such as coronary artery disease, myocardial infarction, acute coronary syndrome and ST segment elevation myocardial infarction (Bilgir et al ., ; Sun et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Several systematic reviews and metaanalyses evaluated the relationship between fetuin-A levels and the risk of CVDs. They provided contradictory results: the association with CVD risk in various prospective studies was found as a negative correlation (decreased serum fetuin-A level correlated with the development of CVDs) [53], as re ecting the progression of CVDs [54], or as inconsistent [55].…”
Section: Fetuin Role In Cvdmentioning
confidence: 99%
“…Higher fetuin-A circulation level in healthy diabetic and non-diabetic subjects without vascular pathology, correlated with CVD risks. However, a contradictory relationship was demonstrated in patients with established vascular disease [53]. It was assumed that in early CVD stages fetuin-A aggravates disease development due to induced insulin resistance and dyslipidemia.…”
Section: Fetuin Role In Cvdmentioning
confidence: 99%